Increasing the competitiveness of an enterprise based on a logistics information system - Wang, Guoyin (Харківський національний автомобільно-дорожній університет, 2025)
The purpose of the study is to develop measures to improve the competitiveness of the organization based on the implementation of a logistics information system. The relevance of the research topic lies in the fact that the competent formation of a logistics system at an enterprise directly affects the competitiveness and profitability of the enterprise, based on theoretical material on the topic, the basic concepts and indicators for assessing the effectiveness of the logistics information system are formed; the financial condition of the enterprise is assessed; the logistics information system at PJSC «Interconditioner» is analyzed, problems and bottlenecks are identified; measures to improve the efficiency of the logistics system of PJSC «Interkonditsioner» are developed; the effectiveness of the proposed measures and their impact on financial results are assessed. The research methods used in the work include observation, comparison, analysis, synthesis, various statistical methods, and forecasting, including the expert method of assessing prospects.
Keywords: competitiveness; logistics; information system; storage; personnel